Jenis Ekstrak Tanaman sebagai Mollusida Nabati terhadap Hama Parmarion martensi pada Tanaman Kubis secara In Vitro - Azwana, Azwana; Kuswardani, Retna Astuti; Sarumaha, Agustinus (Mahesa Research Center, 2025)
Parmarion martensi is a major pest of cabbage crops, causing damage that reduces both quality and market value. The use of botanical pesticides as an alternative control method has not been widely studied. This study aimed to evaluate the effectiveness of extracts from Aegle marmelos (maja fruit), Azadirachta indica (neem leaves), and Carica papaya (papaya leaves) in controlling P. martensi. The experiment was conducted using a Completely Randomized Design (CRD) with 11 treatments and 3 replications. Treatments included a negative control (A0), synthetic pesticide (A1), and plant extracts at concentrations of 20%, 25%, and 30% (A2–A10). The results showed that neem leaf extract at 30% (A7) produced the highest mortality rate, reaching 93.3% at 5 days after application (DAA), with an average feed consumption of 0.39 g/day. Probit analysis indicated an LC₅₀ of 20.3% and an LT₅₀ of 3.6 days, suggesting a strong toxic effect. These findings indicate that neem leaf extract at 30% concentration has potential as a botanical molluscicide to replace chemical pesticides.